Saccharomyces cerevisiae Fermentation Effects on Pollen: Archaeological Implications - Dozier, Crystal A. (Ethnobiology Letters, 2016)
Pollen is the reproductive agent of flowering plants; palynology is utilized by archaeologists because sporopollenin, a major component in the exine of pollen grains, is resistant to decay and morphologically distinctive. Wine, beer, and mead have been identified in the archaeological record by palynological assessment due to indicator species or due to a pollen profile similar to that recovered from honey, a common source of sugar in a variety of fermented beverages. While most palynologists have assumed that pollen grains are resistant to alcoholic fermentation, a recent study in food science implies that pollen is a yeast nutrient because pollen-enriched meads produce more alcohol. The experiment presented here explores the potential distortion of the pollen record through fermentation by brewing a traditional, pollen-rich mead with Saccharomyces cerevisiae. In this experiment, the pollen grains did not undergo any discernible morphological changes nor were distorted in the pollen profile. Any nutrition that the yeast garners from the pollen therefore leaves sporopollenin intact. These results support palynological research on residues of alcoholic beverages and confirms that the fermentation process does not distort the pollen profile of the original substance. The paper concludes with the potential and limits of palynological study to assess fermentation within the archaeological record.